Media Pembelajaran KARPERA Materi Kebutuhan dan Keinginan untuk Meningkatkan Hasil Belajar Siswa Kelas IV SD - Dewi Alvinatur Rohmah; Karimatus Saidah; Wahid Ibnu Zaman (YASIN, 2026)
Instructional media play an important role in helping elementary school students understand abstract concepts through concrete and contextual learning experiences. However, instruction on needs and wants remains dominated by lecture methods and textbook use, resulting in low student engagement and suboptimal learning outcomes. This study aims to develop KARPERA (Budget Planning Cards) instructional media and analyze its validity, practicality, and effectiveness in improving the learning outcomes of fourth-grade elementary school students. The study employed the Research and Development (R&D) method using the ADDIE model, which comprises the Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects were fourth-grade students at SDN Bandar Lor 3, Kediri City. Data were collected through interviews, observations, documentation, validation questionnaires, response questionnaires, and learning outcome tests. The findings indicate that KARPERA media met the validity criteria based on expert assessments, was practical based on teacher and student responses, and was effective in improving learning outcomes on the topic of needs and wants. This study concludes that KARPERA media is suitable for use as an innovative instructional medium that supports contextual learning. These findings provide a practical contribution for teachers in delivering more active and concrete learning and support the development of financial literacy among elementary school students from an early age.